A Brief Review on Cloud Computing Authentication Frameworks - Khan, Abdul Raouf; Alnwihel, Latifa Khalid (Engineering, Technology & Applied Science Research, 2023)
Cloud computing is among the most widely used technologies worldwide as it helps individual users and organizations to store and share information conveniently and cost-effectively. However, data security is a major concern in cloud computing. Security involves guaranteed access to the data only to authorized users and protection against various threats and attacks. Security is generally achieved through the appropriate and efficient implementation of access control, authentication, and authorization mechanisms. Various frameworks have been proposed and implemented for authentication and access control in cloud computing. This paper discusses some of the main authentication frameworks in cloud computing, highlighting their methodologies, algorithms, and problems and identifying the issues that should form the focus of research in the area.